The Relationship Between Traditional Game Gobak Sodor And Motivation To Learn Physical Education In Grade 5 Students of SDN Cikandang - Saputra, Egi Maulana; Sudrazat, Adang; Rukmana, Anin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to explore the relationship between the traditional game Gobak Sodor and students' motivation to learn physical education among 20 fifth-grade students at SDN Cikandang. The research uses a quantitative descriptive method with a survey approach. The normality test results showed a significance value of 0.943, which is greater than 0.05, indicating that the residuals are normally distributed. The homogeneity test also showed a significance value of 0.651, meaning the data is considered homogeneous. In the linearity test, the significance value was 0.304, which is less than 0.05, indicating a linear relationship between the variables. The correlation test revealed a significance value of 0.001 (2-tailed), confirming a significant relationship between the Gobak Sodor game and students' motivation to learn physical education. The Pearson correlation coefficient was 0.975, indicating a strong and positive correlation. This suggests that as participation in Gobak Sodor increases, so does the students' motivation to engage in physical education. In conclusion, the traditional game Gobak Sodor has a positive and meaningful relationship with students' learning motivation in physical education, highlighting its potential as an effective educational tool in elementary schools